Latin America Social work challenges in equity critical moments and the progress of conservatism / Os desafios para o Serviço Social na América Latina em tempo de crise do capital e avanço do conservadurismo - Alayón, Norberto (Textos & Contextos (Porto Alegre), 2016)
The article presents several conceptual considerations on Social Work and lays down different proposals to be taken into account in the construction of a possible agenda for the profession in Latin America. It addresses aspects referring to the professional training of social workers as well as the professional activity in institutions and professional category organization.